Fenomenologia da soldagem MIG/MAG-PV e sua aplicabilidade para juntas sobreposta e em V (passe de raiz) - Nascimento, Alexandre Saldanha do (2011)
The development of electronic power sources has allowed the study of innovative processes, usually with the goal of productivity increase combined to low levels of heat input. The commercially-available processes are based on metal transfer modes and development of waveforms to improve process control. Among those, the MIG/MAG-VP (Variable Polarity) process is a derivative one from the conventional MIG/MAG. It combines the advantages of using positive polarity, such as good arc stability and cathodic cleaning, to the ones provided by negative polarity, which are the high fusion rate of electrode and low heat input to the base metal. However, this process still has limited use due to the lack of technical and scientific literature. Thus, this work presents a thorough investigation of physical aspects, the study of the kinematics of droplets in transfer, the operational performance related to the weld quality and the proposition of a methodology for determination of welding parameters in four waveforms by varying the rate of negative time in order to provide arc stability and suitable metal transfer. The evaluation of the MIG/MAG-PV process was carried out by shadowgraph method and analyses of bead features. Furthermore, the process applicability to lap joints and root pass were also investigated. The MIG/MAG-PV process showed as very effective with satisfactory stability, especially when using waveforms with positive basis before the current pulse. In this condition the droplet in transfer is slowed down and the welding can be considered free of spattering. Test applications in joints showed that the process is robust and allows high productivity.